2016
DOI: 10.1021/acs.nanolett.5b03917
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Optimal Shell Thickness for Self-Catalyzed GaAs/AlGaAs Core–Shell Nanowires on Silicon

Abstract: We present a set of experimental results identifying various effects that govern the carrier dynamics of self-catalyzed GaAs/AlGaAs core-shell nanowires (NWs) grown by molecular beam epitaxy i.e. surface recombination velocity, surface charge traps, and structural defects.Time-resolved photoluminescence of NW ensemble and spatially-resolved cathodoluminescence of single NWs reveal that emission intensity, decay time and carrier diffusion length of the GaAs NW cores strongly depend on AlGaAs shell thickness but… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 48 publications
2
26
1
Order By: Relevance
“…However, for the passivated NW surface with S ≤ 1 × 10 4 cm/s and N TD = N TA = 1 × 10 12 /cm 2 surface recombination does not lead to severe efficiency decrease. Such high quality nanowire surfaces were already achieved for passivated GaAs nanowires [20,42], and should be used in high efficiency nanowire solar cells. Finally, it was shown that surface defects do not directly severely alter the current-matching condition as long as the p − n junction shell stays in the proper partially depleted regime.…”
Section: Surface Recombinationmentioning
confidence: 98%
“…However, for the passivated NW surface with S ≤ 1 × 10 4 cm/s and N TD = N TA = 1 × 10 12 /cm 2 surface recombination does not lead to severe efficiency decrease. Such high quality nanowire surfaces were already achieved for passivated GaAs nanowires [20,42], and should be used in high efficiency nanowire solar cells. Finally, it was shown that surface defects do not directly severely alter the current-matching condition as long as the p − n junction shell stays in the proper partially depleted regime.…”
Section: Surface Recombinationmentioning
confidence: 98%
“…24 This discrepancy can be partly ascribed to the MetalOrganic Vapor Phase Epitaxy The small blue shift observed at low powers, which saturates around 10µW has been also observed for GaAs nanowires capped with AlGaAs shell 26,27 and it was associated with the presence of some negatively charged traps at the interface, which are filled by photo created carriers in the AlGaAs shell, which migrates towards interface. Once filled, they can no longer modify the band bending at the interface, which explains the saturation of the blue-shift of the emission energy above 10µW, indicating that the band bending is the dominant effect in our nanomembranes.…”
mentioning
confidence: 89%
“…Several effects have been reported, such as band bending at the interface leading to the accumulation of the charge at the interface or piezo electric strain. [23][24][25][26][27] In addition, the AlGaAs alloy typically used for capping GaAs nanowires is generally inhomogeneous, with directed and random segregation of Ga and Al forming respectively Al-rich ridges and Ga-rich nanoscale islands . 28,29 Simultaneously, III-V NWs can suffer from twin defects and polytypism, 30,31 which adversely affect their electronic and optical properties.…”
mentioning
confidence: 99%
See 2 more Smart Citations